Impact of the coronavirus pandemic on the functioning of companies from the perspective of employees - Jaworzyńska, Magdalena; Wierzchowska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The main objective of the article is to indicate the impact of the pandemic on the Polish economy, with particular emphasis on businesses from the perspective of employees. The hypothesis is that the coronavirus pandemic negatively affected the functioning of the Polish economy. Taking up this topic is related to the various reactions of the government and European organizations to the emergence of a new threat and the significant role of health in the economy. This article is mainly empirical. The research was conducted using the method of standardized computer-assisted questionnaire interviews between March and April 2021. The questionnaire form was shared on social media in the student group and the group "Accounting – my passion" (in Polish "Księgowość – moja pasja"). 120 entrepreneurs and employees (N=120) were surveyed. The negative impact of the coronavirus is perceived by almost all respondents and the mitigation instruments offered by the government are considered insufficient. It would be worthwhile to think about relief solutions in times of pandemic, the current opinion shows a negative perception of the measures introduced so far. The pandemic caused not only economic effects, but also affected many areas of people’s lives, resulting in a negative perception of reality. The functioning during the lockdown was limited to the necessary minimum, therefore the quality of life was rated as average.
Keywords: functioning of enterprises; pandemic; coronavirus